Hierarchical Carbon Nanowire/Ni@MnO2 Nanocomposites for High‐Performance Asymmetric Supercapacitors. Issue 69 (3rd November 2020) - Kang, Chenxia; Fang, Ju; Fu, Likang; Li, Shuxian; Liu, Qiming
Abstract: A 3D hierarchical carbon cloth/nitrogen‐doped carbon nanowires/Ni@MnO2 (CC/N‐CNWs/Ni@MnO2 ) nanocomposite electrode was rationally designed and prepared by electrodeposition. The N‐CNWs derived from polypyrrole (PPy) nanowires on the carbon cloth have an open framework structure, which greatly increases the contact area between the electrode and electrolyte and provides short diffusion paths. The incorporation of the Ni layer between the N‐CNWs and MnO2 is beneficial for significantly enhancing the electrical conductivity and boosting fast charge transfer as well as improving the charge‐collection capacity. Thus, the as‐prepared 3D hierarchical CC/N‐CNWs/Ni@MnO2 electrode exhibits a higher specific capacitance of 571.4 F g −1 compared with those of CC/N‐CNWs@MnO2 (311 F g −1 ), CC/Ni@MnO2 (196.6 F g −1 ), and CC@MnO2 (186.1 F g −1 ) at 1 A g −1 and remarkable rate capability (367.5 F g −1 at 10 A g −1 ). Moreover, asymmetric supercapacitors constructed with CC/N‐CNWs/Ni@MnO2 as cathode material and activated carbon as anode material deliver an impressive energy density of 36.4 W h kg −1 at a power density of 900 W kg −1 and a good cycling life (72.8 % capacitance retention after 3500 cycles). This study paves a low‐cost and simple way to design a hierarchical nanocomposite electrode with large surface area and superior electrical conductivity, which has wide application prospects in high‐performance supercapacitors. Abstract : Supercapacitive nanoarchitectures : A rationally designed 3D hierarchical carbon cloth/nitrogen‐doped carbon nanowires/Ni@MnO2 (CC/N‐CNWs/Ni@MnO2 ) nanocomposite was prepared by electrodeposition and used as a supercapacitor cathode exhibiting high surface area, outstanding electrical conductivity, and excellent performance in supercapacitors.